Contribution to the Evaluation of Physicochemical Properties, Total Phenolic Content, Antioxidant Potential, and Antimicrobial Activity of Vinegar Commercialized in Morocco - Mohammed Kara; Amine Assouguem; Mohamed El Fadili; Safaâ Benmessaoud; Samar Zuhair Alshawwa; Omkulthom Al Kamaly; Hamza Saghrouchni; Abdou Rachid Zerhouni; Jamila Bahhou (Molecules, 2022)
Vinegar is a natural product widely used in food and traditional medicine thanks to its physicochemical properties and its richness in bioactive molecules. However, its direct use by consumers can have complications and undesirable effects. Therefore, this study contributes to investigating the physicochemical and biological properties of eleven vinegars marketed in Morocco. Determination of pH, acetic acid, conductivity, total soluble solids and alcohol content in vinegar was carried out. The polyphenols (TP), flavonoids (TF), and condensed tannins (CT) content was determined, and their antioxidant activities were evaluated using 2,2-diphenyl-1-picryl Hydrazyl (DPPH), Ferric Reducing Antioxidant Power (FRAP) and Phosphomolybdenum Reduction Assay (TAC). Then, the antimicrobial activity was studied against four pathogenic bacteria and two fungal strains, using the disk diffusion and the microdilution method. This study showed a wide range of acetic acid values from 0.65 ± 0.29 to 5.15 ± 0.20%. The high value of TP, TF, and CT in our samples V10, V9, and V4 was 655.00 ± 22.2 µgGAE/mL, 244.53 ± 11.32 µgQE/mL and 84.63 ± 1.00 µgTAE/mL, respectively. The tested strains showed variable sensitivities to the different samples with inhibition zones ranging from 6.33 ± 2.08 to 34.33 ± 0.58 mm. The lowest minimum inhibition concentrations were recorded against Staphylococcus aureus ATCC29213 ranging from 1.95 to 7.81 µL/mL. While Aspergillus niger ATCC16404 showed resistance against all of the analyzed samples. In general, vinegar commercialized in Morocco presents a variable range of products with variable properties. Indeed, must take into account this diversity when using it. A future study is needed to identify the phytochemical composition that will further the comprehension of this variability and contribute to its valorization.